Breaking out of the box : interdisciplinary collaboration and faculty work - Amey, Marilyn J.; Brown, Dennis F. (Emerald Publishing Limited : Information Age Publishing, 2004)
Presents a discussion of concepts and definitions of interdisciplinarity and collaboration, and introduces a model of Interdisciplinary Collaboration. Examines how the Interdisciplinary Collaboration model and concepts make sense in academic organizations and affect academic work.